Paninian Studies Professor S. D. Joshi Felicitation Volume - Deshpande, Madhav; Bhate, Saroja (Michigan Papers On South And Southeast Asia, 2020)
Pa?ini's grammar is the oldest surviving grammar of Sanskrit, dating back to the fifth century BCE. In its completeness of coverage of linguistic elements and its theoretical and analytical sophistication, Pa?ini's grammar is surprisingly modern. It has long provided inspiration for many ideas in modern linguistics, and continues to attract scholars' attention in the fields of Sanskrit and linguistics. Pa?inian Studies collects seventeen essays on Pa?inian linguistics in a single volume dedicated to Professor S. D. Joshi, a stalwart scholar of Pa?inian grammar. The contributors, all scholors of international acclaim and students and friends of Professor Joshi, include Ashok Aklujkar, Pandit V. B. Bhagwat, Saroja Bhate, Gopikamohan Bhattacharya, Johannes Bronkhorst, George Cardona, Achyutananda Dash, Madhav M. Deshpande, Peter Edwin Hook, Daniel H. H. Ingalls, V. N. Jha, Dinabandhu Kar, Paul Kiparsky, Bimal Krishna Matilal, G. B. Palsule, K. Kunjunni Raja, and J. A. F. Roodbergen. Taken together, their contributions encompass the wide range of interests and specializations within the field of Pa?inian studies.